The growth of Islamic finance and banking : innovation, governance and risk mitigation - Qādrī, Ḥusain Muḥīuddīn; Bhatti, M. Ishaq (Abingdon, Oxon ; New York, NY : Routledge, 2020)
This book covers the recent literature concerning Islamic banking and finance (IBF), focuses on the history of IBF since its inception and introduces the latest innovative concepts and practices in the field. The authors cover important topics such as the role of ownership, Shari`ah compliance and governance structures in raising debt capital using IBF practices, including Fatwa issues and the use of benchmarking practices. The book also addresses topics like archival data, the influence of leverage on ownership structure, and sukuk structures, as well as misconceptions, threats, challenges and opportunities in IBF. Finally, the book deals with prominent issues such as business score-carding, Takful (Islamic Insurance), IBF implications for block-chain-based fintech and finance hub concepts in Islamic microfinance models. This edited volume is an important contribution to the IBF literature as it provides a much-needed in-depth look into industry practices through the perspective of corporate finance and governance. With its interdisciplinary approach covering legal and financial issues along with a wide variety of notable contributors, this book will be a valuable reference guide to both teachers and students of Islamic banking and economics.
Contents:
Introduction

Chapter 1

Standardization in the Islamic Banking & Financial System: The Methodology of Inclusion (Taqlid al-Madhahib)

Chapter 2

Recent Development in Islamic Finance and financial products

Chapter 3

On the role of ownership and governance structure in raising capital: A sukuk example

Chapter 4

Takāful (Islamic Insurance) on the Blockchain

Chapter 5

IT Based Finance Hub: A New Horizon towards Transparent Zakat Distribution Model *

Chapter 6

The Way Towards Standardizing Islamic Economic, Financial and Banking Fatawa

Chapter 7

The Fallacy of Conventional Benchmarks in Islamic Banking and Finance: Defining,
Contents: Defending and Discussing with Evidence from Archival Data

Chapter 8

Influence of Leverage on Ownership Structure-Performance Relationship: A Panel Data Approach of Islamic & Conventional Banks of Pakistan

Chapter 9

Dynamic correlation and volatility linkage between stocks and sukuk

Chapter 10

Provision of Riba by Religious Faith: A Comparative Analysis

Chapter 11

Layers of Misconceptions about Islamic Banking: Are Islamic Banks Threats, Challenges and Opportunities for Investors

Chapter 12

Overview of Progress in Islamic Commercial and Social Finance in Pakistan

Chapter 13

Translation of Economic Verses by Shaykh-ul-Islam Dr Muhammad Tahir-ul-Qadri in the Light of Translation Studies: A Linguistic Translational Comparative Analysis

Chapter 14

Drawing inferences from Ali ibn Abi Talib’s Teachings on social,
Contents: and collective responsibility for a fair and just economy

Chapter 15

Pricing anomaly: Tale of two similar credit-rated bonds with different yields

Chapter 16

Resolving Islamic Finance Disputes through Arbitration in the Middle East

Chapter 17

Formation of Tangible-Intangible Capital and Venture Philanthropy: An Innovation in Islamic Finance

Chapter 18

Theoretical, Practical vis-a-vis Legal Development in Islamic Banking: A case of Pakistan

Chapter 19

Islamic Safety Nets for the Poor: Pakistan’s Experience

Concluding Remarks on the Growth of the IBF Industry
Includes bibliographical references and index.
BBS
Trim Education
Keywords: Finance -- Islamic countries; Finance -- Religious aspects -- Islam; Banks and banking -- Islamic countries; Banks and banking -- Religious aspects -- Islam; Business & finance